Determinantes do comprometimento organizacional: uma avaliação na Petrobras\Lubnor - Cunha, Maria Cristiane (2009)
In recent years, special attention has been given by organizational commitment researchers to the validation of the diagnosis instrument and, therefore, of the conceptualization model of three components of organizational commitment developed by Meyer and Allen (ALLEN and MEYER, 1990, 1996; MEYER AND ALLEN, 1984, 1991, 1997; MEYER, ALLEN AND SMITH, 1993). For these authors, organizational commitment has three components/bases: affective, instrumental and normative. The main objective of the research was to identify and evaluate the compromise that influences the performance of the work force at Petrobras\Lubnor. The research was based on the work of Meyer, Allen and Smith (1993), taking into account the context in which currently is Petrobras\Lubnor. The methodology procedure for the proposed objectives allows us to classify this work as a case study, exploratory research regarding its objectives, regarding the nature as a quantitative research, since the data collected in the form of questionnaire have been subjected to a statistical treatment, and qualitative, since interviews were conducted with the labor force for validation of statistical data. Regarding the procedures, the survey was used, with structured questionnaire and interviews. The questionnaire was designed based in the dimensions of compromise established by Meyer, Allen and Smith (1993), totaling 18 questions, 6 for each dimension. The questionnaire was applied by the researcher with 233 persons among employees and contractors. The interviews were applied to 18 strategical employees and contractors. The questionnaires collected have been subjected to a statistical treatment for problem analysis and content analysis for the interviews. The research results show positive organizational commitment at Petrobras\Lubnor. Based on the control variable crossover, the conclusion is that in the workforce dominates affective commitment, and the employees are more committed, genre does not affect commitment and the senior workforce is more compromised. The Unit Strategic Plan (PGUN) follow-up indicates attention to a better communication within the Organization, both among the managerial level and the workforce, to expand its use and improve the results of the commitment, making it more productive in the current context of innovation and enterprise competitiveness.